Experimental studies of mitigating premixed flame-excited thermoacoustic oscillations in T-shaped Combustor using an electrical heater - Wu, Gang (2021)
In this work, attenuating unsteady heat-driven thermoacoustic oscillations in a T-shaped standing-wave Rijke-type combustor is numerically and experimentally studied. For this, 2D numerical studies are conducted first on a T-shaped standing-wave combustor. In such combustor, a heater with constant surface temperature of 1100 K is confined in the bottom branch. However, a secondary heater with a controllable surface temperature is enclosed in the horizontal bifurcating branch. When the secondary heater is not actuated, large-amplitude limit cycle oscillations are successfully generated. However, as the secondary heater surface temperature is increased to 1600 K, the limit cycle oscillations are completely mitigated. To validate these findings, experimental study is then conducted on a T-shaped combustor. A premixed flame is enclosed in the bottom branch and an electrical heater is implemented to attenuate unstable combustion oscillations generated by the flame. When the electrical heater is not actuated, premixed flame-excited thermoacoustic oscillations are generated at approximately 210 Hz. However, with the heater being actuated, sound pressure level is successfully reduced from 130 dB to 85 dB. The present work opens up an alternative control approach to enable combustors being operated stably.